2013
DOI: 10.1111/jcc4.12048
|View full text |Cite
|
Sign up to set email alerts
|

A New Space for Political Behavior: Political Social Networking and its Democratic Consequences

Abstract: Social networking sites (SNS) currently boast more than half a billion active users worldwide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
1
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(150 citation statements)
references
References 42 publications
8
127
1
10
Order By: Relevance
“…Our results suggest that Facebook activity merits a more nuanced approach than traditional measures, which often combine diverse ways of consuming and expressing views on the social media site (Bode et al, 2014;Vitak et al, 2011). In this study, we distinguish between three types of Facebook activity: news consumption, news expression, and issue-specific engagement.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our results suggest that Facebook activity merits a more nuanced approach than traditional measures, which often combine diverse ways of consuming and expressing views on the social media site (Bode et al, 2014;Vitak et al, 2011). In this study, we distinguish between three types of Facebook activity: news consumption, news expression, and issue-specific engagement.…”
Section: Discussionmentioning
confidence: 88%
“…Facebook activities such as sharing links and liking pages can contribute to an individual's self-perceptions about their role in the political process on a particular issue in several ways, including by building the vocabulary and skills related to public activism or by publicly committing oneself to a position (Bode et al, 2014;Pingree, 2007;Thorson, 2012;Verba et al, 1995). Further, these Facebook activities may also encourage a retrospective evaluation of one's own attitudes, as selfperception theory might suggest (Bem, 1972; see also Ikeda et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Con respecto a la primera categoría, nos hemos propuesto esclarecer si, en efecto, existe una relación entre la participación política de los jóvenes colombianos en los medios sociales, tal y como ha sido avistada en otros contextos (Park, Kee & Valenzuela, 2009;Bode et al, 2014); asimismo, también resulta pertinente observar cómo influye dicha participación en línea, con la participación política fuera de línea como segunda categoría, una interacción que ha sido ya abordada por la literatura previa (Verba, 1962;Brady, Verba & Lehman, 1995;Estrada, 1995;, si bien aún no hemos encontrado un estudio sobre el caso de Colombia que se haya detenido en este fenómeno. De igual manera, consideramos importante tomar en cuenta la tercera categoría, la cual señala en qué medida ha cambiado el consumo de medios tradicionales en el grupo poblacional escogido, y de qué manera el surgimiento de los medios digitales coexiste o ha comenzado a reemplazar la forma tradicional de informarse (Delarbre, 2011;Arellano, 2013;Villamil, 2017).…”
Section: Objetivosunclassified
“…Early research suggests that, while overall Internet use by itself does not necessarily lead to political participation, there has been substantial evidence showing a positive impact of Internet use for political purposes on participation (Boulianne, 2009). With the rise of social media since the late 2000s, a bourgeoning literature has also shown that using social media for seeking public affairs information, opinion expression, and/or mobilization can lead to both online and offline political participation (e.g., Bode et al, 2014;Conroy et al, 2012;Dimitrova et al, 2014;Enjolras et al, 2013;Macafee and De Simone, 2012;Skoric and Poor, 2013;Tang and Lee, 2013;Towner, 2013;Valenzuela, 2013).…”
Section: Introductionmentioning
confidence: 98%